P‐8: Analysis of Degradation Mechanism of Oxide Semiconductor FETs with High Tolerance to Intense NBTIS. Issue 1 (28th June 2022) - Hosaka, Yasuharu; Obonai, Toshimitsu; Dobashi, Masayoshi; Nakayama, Tomonori; Shima, Yukinori; Ohno, Masakatsu; Yamazaki, Shunpei
Abstract : This work verifies the existence of more than one cause of NBTIS degradation of oxide semiconductor FETs by analyzing its time dependence. As defects in a gate insulator (GI) that cause NBTIS degradation, indium diffused into the GI also serves as hole trap defects besides the NBOHC defects proposed by Tsubuku et al.